On Lie Structure in Semiprime Inverse Semirings - Ibraheem, Rawnaq KH.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2019)
In this paper we introduce the definition of Lie ideal on inverse semiring and we generalize some results of Herstein about Lie structure of an associative rings to inverse semirings.